2017
DOI: 10.1177/0363546517734508
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 Exercise Rehabilitation Programs for Multidirectional Instability of the Glenohumeral Joint: A Randomized Controlled Trial

Abstract: For people with MDI, 12 sessions of the Watson MDI program were more effective than the Rockwood program at 12- and 24-week follow-up. Registration: ACTRN12613001240730 (Australian New Zealand Clinical Trials Registry).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(134 citation statements)
references
References 56 publications
7
118
0
Order By: Relevance
“…It was aimed to reinforce muscle strength around the shoulder joint [8]. In contrast, the Watson program includes plyometric exercise, functional training, and movement-specific training [7]. The latter program and concept would have a better effect on this patient, in order to acquire dynamic stability of the shoulder joint during movement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was aimed to reinforce muscle strength around the shoulder joint [8]. In contrast, the Watson program includes plyometric exercise, functional training, and movement-specific training [7]. The latter program and concept would have a better effect on this patient, in order to acquire dynamic stability of the shoulder joint during movement.…”
Section: Discussionmentioning
confidence: 99%
“…EDS patients usually suffer from many musculoskeletal symptoms, even when they grow up [4]. On the other hand, it has been demonstrated that patients who have shoulder MDI will recover shoulder function during movement after rehabilitation programs [7,9]. However, the prognosis of this patient was challenging because patients with EDS were excluded from the rehabilitation programs.…”
Section: Examinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The exercise programmes were all safe and not likely to cause injury. Previous studies have reported that approximately 1% of adolescents had systemic multiligament laxity, which can easily lead to shoulder, elbow and wrist injuries during exercise training [18,19]. Therefore, we did not include pull-up, push-up, or other limb anti-resistance training exercises.…”
Section: Discussionmentioning
confidence: 99%